2013
DOI: 10.1186/1472-6963-13-22
|View full text |Cite
|
Sign up to set email alerts
|

Service quality, trust, and patient satisfaction in interpersonal-based medical service encounters

Abstract: BackgroundInteraction between service provider and customer is the primary core of service businesses of different natures, and the influence of trust on service quality and customer satisfaction could not be ignored in interpersonal-based service encounters. However, lack of existing literature on the correlation between service quality, patient trust, and satisfaction from the prospect of interpersonal-based medical service encounters has created a research gap in previous studies. Therefore, this study atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
182
4
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(218 citation statements)
references
References 34 publications
17
182
4
8
Order By: Relevance
“…As table 1 illustrates, all the Cronbach's α values exceeded 0.7, meeting the acceptable standard of more than 0.7, and no single factor included only one question. (9,25) The analytical results of all scales had reached this standard.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As table 1 illustrates, all the Cronbach's α values exceeded 0.7, meeting the acceptable standard of more than 0.7, and no single factor included only one question. (9,25) The analytical results of all scales had reached this standard.…”
Section: Instrumentsmentioning
confidence: 99%
“…These are all issues that citizens consider when choosing a medical service provider, and the concept of these service encounter attributes is highly similar to some perspectives of service quality. (8)(9)(10) It is used experimental design methods to investigate the factors influencing customer evaluations and responses when service encounter occurs. This study held that adding new 3Ps (physical evidence, people [including frontline staff and customers], and process) to the 7Ps of service marketing can concretely present service encounter to customers.…”
Section: Introductionmentioning
confidence: 99%
“…(Chang, Chen, & Lan, 2013) menjelaskan bahwa pelayanan pada rumah sakit memerlukan interaksi yang tinggi antara pasien dengan penyedia jasa seperti dokter, suster dan paramedik. Interaksi ini apabila berlangsung dengan baik akan menyebabkan persepsi konsumen akan kualitas jasa rumah sakit tersebut baik dan akhirnya akan menghasilkan kepuasan pasien (Chang, Chen & Lan, 2013).…”
Section: Kualitas Pelayananunclassified
“…(Chang, Chen, & Lan, 2013) menjelaskan bahwa pelayanan pada rumah sakit memerlukan interaksi yang tinggi antara pasien dengan penyedia jasa seperti dokter, suster dan paramedik. Interaksi ini apabila berlangsung dengan baik akan menyebabkan persepsi konsumen akan kualitas jasa rumah sakit tersebut baik dan akhirnya akan menghasilkan kepuasan pasien (Chang, Chen & Lan, 2013). Begitu juga penelitian yang dilakukan oleh (Aghamolaei et al, 2014) di Iran, mereka berusaha mengevaluasi kualitas pelayanan rumah sakit di Iran dan menemukan bahwa ternyata persepsi pasien di Iran mengenai dimensi kualitas yang paling tinggi adalah assurance atau jaminan bahwa rumah sakit mempunyai tenaga yang handal sehingga pasien percaya.…”
Section: Kualitas Pelayananunclassified
“…In fact, both physicians and patients need to engage in an interactive process because of the uncertainties and complex process of medical treatment. Various studies on relationship marketing have confirmed that a good relationship quality is based on a long-term relationship between patients and hospitals [4], [5], and this high-quality relationship is an essential component that leads to a sustainable development for hospitals in a competitive medical service industry [6]. However, empirical practices of healthcare organizations concerning the enhancement of patient loyalty through maintenance of good relationships with patients are still ambiguous [7].…”
Section: Introductionmentioning
confidence: 99%